Genotoxic effect of iron overload and disease complications in transfused β thalassaemic patients. (8th December 2016) - Ferro, Elisa; Visalli, Giuseppa; La Rosa, Maria Angela; Piraino, Basilia; Civa, Rosa; Randazzo Papa, Gaetano; Di Pietro, Angela
Abstract: In previously reported studies, we observed significantly high genotoxicity biomarkers in regularly transfused thalassaemic patients, thus, in this study, we better investigated the genotoxic effect of iron overload and of thalassaemia complications, including their drug treatments. The assessment was performed in 64 regularly transfused thalassaemic patients using cytokinesis-block micronucleus and comet assays. All patients were splenectomised and undergoing iron chelation therapy. To reduce hypoxia-induced oxidative damage, the patients with haemoglobin levels <9.5 g/dL were excluded. Serum concentrations of ferritin, iron, transferrin and the percentage of transferrin saturation, as well as cardiac and hepatic T2* magnetic resonance imaging, were considered to evaluate serum and organ siderosis. All genotoxic biomarkers significantly differed between patients and healthy subjects. Iron intake via blood transfusions was inversely related to percentage of DNA in tail. The disease complications affecting endpoints were active Hepatitis C virus infection, drug therapy for osteoporosis (i.e. bisphosphonates) and hormone replacement therapy for hypogonadism. The results, highlighting the combined effect of iron overload and, mainly, disease complications, including their respective pharmacological treatments, confirmed the increased cancer risk in thalassaemic patients.